2021
DOI: 10.1111/ppc.13012
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of the life satisfaction and psychological well‐being of nursing students on their happiness levels

Abstract: Purpose This study aims to examine the effect of nursing students' life satisfaction and psychological well‐being on their perceived happiness levels. Method The study, which was designed as a descriptive and cross‐sectional study was carried out in Turkey with 264 students of nursing. Findings Students' life satisfaction and happiness (r = 0.722), psychological well‐being and happiness (r = 0.743), and psychological well‐being and life satisfaction (r = 0.689) were found to be positively and highly correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As an important element in happiness, life satisfaction is the gap between what people have and what they want ( 14 ), which correlates positively with academic performance and productivity ( 15 ). It is believed that life satisfaction is affected by conditions such as health, socioeconomic status, and activities ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an important element in happiness, life satisfaction is the gap between what people have and what they want ( 14 ), which correlates positively with academic performance and productivity ( 15 ). It is believed that life satisfaction is affected by conditions such as health, socioeconomic status, and activities ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, individual and organizational predictors determine the happiness of nurses [ 8 , 9 ]. However, investigators found that nursing students often face stressful periods during their studies, in addition to factors such as life satisfaction, psychological wellbeing, and quality of life, which influence happiness among nursing students [ 9 , 13 , 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A measure of happiness was used in this study as a known correlate to both spirituality and health [ 23 , 24 ]. Happiness was assessed using the Subjective Happiness Scale (SHS), a four-item scale measuring general happiness from intrinsic and relative perspectives [ 25 ].…”
Section: Methodsmentioning
confidence: 99%